Identification of the Combustion Engine Resistance to Motion Torque Components - Antoni Iskra; Maciej Babiak; Jaroslaw Kaluzny (Communications, 2011)
Identification of the combustion engine resistance to motion is necessary in all investigations aimed at limiting frictional losses. Despite many attempts to measure the frictional resistance components, there are still no functional test beds that would allow to take measurements of frictional force or frictional torque in particular units. Most often the mean value of the torque for one or even two full revolutions of the crankshaft is determined. For many reasons it is more convenient to determine the resistance to motion torque of the combustion engine with an external drive but unfortunately, the torque from the external drive is disturbed by torsional vibration. There is at least a theoretical possibility of separating the torque generated by vibration from the raw measuring signal. In the paper, the results obtained as well as selected problems of such separation are presented.